DESKRIPSI KETERAMPILAN PSIKOMOTORIK SISWA KELAS XI IPA SMAS MUJAHIDIN PONTIANAK PADA PRAKTIKUM TITRASI ASAM-BASA - Kurniawan, Novan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this research was to describe psychomotor skill of students on grade XI Mujahidin Senior High School in acid-base titration practicum. The research form was descriptive method using observation data collection technique and interview. The research subjects was students of grade XI Mujahidin Senior High School in academic year 2016/2017 who consist of 60 students. The results of data analysis showed that psychomotor skill on the aspect of determining what will be implemented in the form of work steps was 59.32%, class feld as good category. Psychomotor skills on the aspect of organizing and submitting reports systematically, knowing how to use the tools, and speed in completing all phases in the practicum lab were 42.3%, 42.3% and 20.3% respectively. These results that the psychomotor skills of in acid-base titration practicum on grade XI Mujahidin Senior High School were good.  Keywords: Psychomotor skills, titration,  acid-base